Hepatic arterial infusion chemotherapy versus sorafenib for advanced hepatocellular carcinoma with portal vein tumor thrombus: An updated meta-analysis and systematic review - Zhang, Wei; Ouyang, Deliang; Huang, Zhangkan; Che, Xu (Frontiers in Oncology, 2023)
Background: Sorafenib was the first drug approved for advanced hepatocellular carcinoma (HCC). However, it is limited by poor efficacy for HCC with portal vein tumor thrombus (PVTT). Some studies suggested that hepatic artery infusion chemotherapy (HAIC) could provide survival benefits to patients with advanced HCC with PVTT. Aim: The study aimed to compare the efficacy of HAIC versus sorafenib in patients with HCC accompanied by PVTT. Methods: The PubMed, Embase, and Cochrane Library databases were searched for studies published until September 2022. Statistical analyses were performed using Stata SE 15 software. Results: Eight studies with 672 patients, 403 in the HAIC group and 269 in the sorafenib group, were included in the meta-analysis. The rates of complete response (RR=3.88, 95%CI:1.35-11.16, P=0.01), partial response (RR=3.46, 95%CI:1.94-6.18, P<0.0001), objective response rate (RR=4.21, 95%CI:2.44-7.28, P<0.00001) and disease control rate (RR=1.73, 95%CI:1.28-2.35, P=0.0004) were significantly higher in the HAIC group compared to the sorafenib group, whereas the progressive disease rate (RR=0.57, 95%CI:0.40-0.80, P=0.02) was significantly lower in the former. In contrast, the stable disease rate (RR=1.10, 95%CI (0.69-1.76), P=0.68) was similar in both groups. The overall survival (HR=0.50, 95%CI:0.40-0.63, P<0.05) and progression-free survival (HR=0.49, 95%CI:0.35-0.67, P<0.05) rates were significantly higher in the HAIC group compared to the sorafenib group. Conclusion: HAIC has better efficacy against HCC with PVTT than sorafenib and may be considered an alternative to the latter. However, more high-quality randomized control trials and longer follow-ups are needed to verify our findings.